2012
DOI: 10.1007/s00464-012-2716-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of gastric bypass and duodenal switch on systemic exposure of atorvastatin

Abstract: BackgroundA previous study of 22 patients undergoing either gastric bypass or duodenal switch showed increased systemic exposure of atorvastatin acid 3–8 weeks after surgery in the majority of patients. This study aimed to investigate the long-term effects on systemic exposure of atorvastatin acid in the same group of patients.MethodsAn 8-h pharmacokinetic investigation was performed a median of 27 months (range 21–45 months) after surgery. Systemic exposure was measured as the area under the plasma concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…RYGBP was the predominant surgical procedure (n = 18) . In one study, BPD was investigated as the surgical procedure, while two studies investigated BPD‐DS, six studied SG, and one included jejunoileostomy …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RYGBP was the predominant surgical procedure (n = 18) . In one study, BPD was investigated as the surgical procedure, while two studies investigated BPD‐DS, six studied SG, and one included jejunoileostomy …”
Section: Resultsmentioning
confidence: 99%
“…Among the 22 studies, 16 utilized a single‐dose design, administering a given dose of the studied drug on the day of the pharmacokinetic study intervention. In the remaining six studies, patients were investigated in steady state . Several drugs were studied because of their status as probe drugs/substrates for different CYP enzymes and drug transporters, eg, midazolam for CYP3A as well as digoxin for P‐gp .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the few studies addressing this issue demonstrated that the systemic exposure of atorvastatin showed a significant change over time after bariatric surgery, albeit with large inter- and intra-individual variations. The findings indicate that patients using atorvastatin or drugs with similar pharmacokinetic properties should be monitored closely for both therapeutic effects and adverse events during the first years after gastric bypass and duodenal switch [77]. …”
Section: Management Of Co-morbiditiesmentioning
confidence: 99%
“…However, treatment with statins should be initiated if treatment targets are not met on lifestyle intervention [64]. Since the long-term effect of bariatric surgery on the absorption and pharmacokinetics of statins is largely unknown [76], patients on statins should be treated with the lowest dose possible while monitoring the plasma lipid profile [76,77]. One of the few studies addressing this issue demonstrated that the systemic exposure of atorvastatin showed a significant change over time after bariatric surgery, albeit with large inter- and intra-individual variations.…”
Section: Management Of Co-morbiditiesmentioning
confidence: 99%